Antimycobacterial activity of certain mangrove plants against multi-drug resistant Mycobacterium tuberculosis - Prabu, Amudha; Seenivasan, Prabu; Kumar, Vanaja (Asian Journal of Medical Sciences, 2014)
Objectives: The present study was conducted aiming to identify a potent mangrove plant against Mycobacterium tuberculosis using rapid method, luciferase reporter phage (LRP) assay. Methods: Seven mangrove plants viz., Ceriops decandra, Aegiceras corniculatum, Excoecaria agollacha,Avicennia officinalis, Rhizophora mucronata, Suaeda monoica and Sesuvium portulacastrum were collected from Pichavaram mangrove forest in the east coast of, Tamil Nadu. Hexane and methanol extracts were obtained and antimycobacterial activity was done by LRP assay at the concentration of 500 μg/ml. Mycobacterial strains viz. reference strain M. tuberculosis H37Rv and two clinical isolates of M. tuberculosis, one sensitive and the other resistant to Streptomycin, Isoniazid, Rifampicin and Ethambutol used for this study. Results: Methanol extract of E. agollacha showed maximum antimycobacterial activity followed by A. corniculatum and A. officinalis at 500 μg/ml concentration. The remaining four plants (Suaeda monoica, Sesuvium portulacastrum, R. mucronata and C. decandra) showed less or no activity. However, hexane extracts of all the tested plants failed to inhibit the mycobacterial strains. Conclusions: Among the seven plants tested, E. agollacha was found to have better anti-TB activity. Further studies based on bioassay guided fractionation and phytochemical analysis may useful to identify the potent antimycobacterial molecule(s) from this mangrove plant. Asian Journal of Medical Science, Volume-5(3) 2014: 54-57 http://dx.doi.org/10.3126/ajms.v5i3.9171